Grammaticality Of Subject-Verb Agreement In Pakistani English - Mir, Shahid Hussain; Ashiq, Mahwish; Shafi, Dr. Sehrish (Migration Letters, 2024)
This research paper investigates the grammaticality of subject-verb agreement in Pakistani English (PE), focusing on the variation and patterns observed in this linguistic aspect. The study adopts a descriptive approach, analyzing written and spoken data collected from various sources, including academic texts, news articles, and spoken interactions. The analysis encompasses both native and non-native speakers of English in Pakistan, aiming to understand how subject-verb agreement is realized across different contexts and by speakers with varying levels of proficiency. The findings reveal a complex picture of subject-verb agreement in PE, characterized by a range of grammatical patterns influenced by factors such as regional dialects, educational background, and exposure to English varieties. While some instances of non-standard agreement are identified, indicating potential areas of difficulty or transfer from other languages, the overall picture suggests a growing awareness and adherence to standard English norms in formal written contexts. This research contributes to the ongoing discussion on World Englishes and the development of English as a global language, highlighting the dynamic nature of linguistic norms and usage in diverse sociolinguistic contexts like Pakistan. The implications of these findings extend to language teaching and assessment practices, emphasizing the need for a nuanced understanding of language variation and proficiency in English language education in Pakistan.